Fabrication of three dimensional micro-components – A review - Ali, Mohammad Yeakub; Hung, Wayne N.P. (2000)
Micro-components have become increasingly important to meet the demand of miniaturization and have a wide variety of applications in the field of micro-electronics, opto-electronics and microelectromechanical systems. Lithography, electron beam machining (EBM), laser beam machining (LBM), focused ion beam (FIB) machining are mostly being used for the machining of two-dimensional (2D) and pseudo three dimensional (3D) micro-components. But it was more difficult to fabricate 3D micro-components with curved surfaces by these processes. In the recent years, LIGA (Lithography, Electroplating and Molding) technique has evolved as a promising method for mass fabrication of 3D micro-components at high expenses and investment. This paper reviews the available fabrication processes for 2D and 3D micro-components. It covers the fundamentals, applications and limitations of each process.